(untitled) (Applied Biological Research, 2016)
Silkworm, Bombyx mori (L.), is susceptible to several diseases and no breed so far is reported to be immune. In the present investigations, 41 silkworm breeds of varied geographical origin were evaluated for their susceptibility to Bombyx mori nuclear polyhedrosis (BmNPV) and bacterial flacherie under natural conditions. Significant difference was observed in larval and pupal mortality due to both nuclear polyhedrosis and bacterial flacherie. The highest larval mortality (9.29%) was observed in ‘M57’ due to nuclear polyhedrosis and least (0.77%) in ‘NB4D2’ and ‘SI(P)’. The larval mortality due to flacherie ranged from 0.67 to 7.22%. A significant variation was observed in pupation rate and highest pupation was noticed in ‘Jam10’ (95.31), followed by ‘S1M’ (95.27), ‘BL1’(95.10), ‘CP1A’(94.66), ‘Pure81’, (94.56), ‘CPIB’ (94.33), ‘S1P’(94.21), ‘Chinese Farmer’ (94.19), ‘Chakwi’ (94.09) and ‘Chinese D4’(94.03) which were statistically at par with one onother.